‘You’re ignoring the truth’ – Fatih Akın’s Polluting Paradise (2012) and Eco-Trauma Cinema - Domalewski, Adam (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The paper provides an analysis of the documentary Polluting Paradise (2012) by Fatih Akın within the context of eco-trauma cinema. The movie depicts ecological contamination as a social problem and mutual catastrophe, exactly as the theory of eco-trauma cinema suggests. Through a careful observational mode of filmmaking that characterize Polluting Paradise, the mechanisms that are responsible for environmental pollution are being scrutinized. The author argues that the movie combines documentary techniques with melodramatic structures for the sake of the audience’s emotional involvement. The article concludes with a reflection on the cinematic rhetoric used by Akın to affect the viewers.